Training of history teachers: the research principle as the foundation of teaching practice - Marlene Rosa Cainelli; Márcia Teté Elisa Ramos; Maria de Fátima da Cunha (Universidade Federal de Santa Catarina, 2016)
Abstract The purpose of this article is to discuss the operating guidelines of supervised intership, of the history course at the Universidade Estadual de Londrina, UEL, Paraná, Brazil, it also aims to reflect on the relationship between theory/practice in the professional training of history. In order to do this, it is necessary to highlight the theoretical and methodological guidelines that establish the basis of the disciplines aimed at the formation of the future history teacher, considering the discipline and its disciplinary code as being important to establish experience in initial formation of History teachers. It is also important to characterize the operation of the training period, its phases, and curriculum organization, the position of the student facing the training period of history, as well as the search and investigation of their ideas on post-regency experience. Starting from the stage reports as a source of this research, the experiences of students in seventh and eighth semester of the history course of the 2010 and 2011years were considered. For the construction of historical literacy, the steps of the history intership and didactic and pedagogical approach to teaching and historical learning demonstrate that the self-History investigative principle was based according to the class-workshop model proposed by Isabel Barca. Keywords: Teacher Training. School Discipline. Coaching.